Business interests above human lives: An analysis of business-related violations in the Kanjuruhan tragedy from a human rights perspective - Muhammad Ammar Darmaputra (PT WIM Solusi Prima, 2026)
The Kanjuruhan Tragedy of 1 October 2022 represents a significant human rights incident that exposed weaknesses in business governance within Indonesia’s sports industry. The event, which resulted in hundreds of deaths and injuries, highlighted the tension between commercial interests and the responsibility to protect human rights. This study aims to examine the business and human rights dimensions of the Kanjuruhan Tragedy through the framework of the United Nations Guiding Principles on Business and human rights (UNGPs) and Presidential Regulation Number 60 of 2023 concerning the National Strategy on Business and human rights. The research employs a normative legal method using statutory, conceptual, and comparative approaches. Data were collected through a literature review of legal instruments, official documents, investigation reports, and relevant academic sources. The findings indicate that the scheduling of the match to accommodate prime-time television broadcasting contributed to excessive crowd density and heightened safety risks. Furthermore, the study identifies failures by business actors and related stakeholders to implement adequate human rights due diligence, risk mitigation measures, and crowd management practices. These shortcomings demonstrate the absence of effective safeguards required under contemporary business and human rights standards. The study concludes that stronger corporate accountability mechanisms, effective implementation of human rights due diligence, and the integration of business and human rights principles into sports event governance are necessary to prevent similar incidents in the future and to ensure greater protection of fundamental rights.